Rock structure and slope stability study of Walling area, central west Nepal (Journal of Nepal Geological Society, 1981)
The author emphasises the urgent need for a potential risk mapping in Nepalese, hills where natural and artificially promoted erosion and slope instability are drastic and threatening the ecological balance. The author describes a potential risk mapping method based   only on   the relationship between the rock structure and topography.This method is applied to an hundred square kilometers area, west of Walling which is crossed by the ro1d Pokhara-Tansen-Butwal (Siddartha Highway). The author finds that this method is fast and gives a good picture or the condition or the terrain.